Dinamika Struktur Aktiva, Pertumbuhan Penjualan, dan Risiko Bisnis dalam Penentuan Harga Saham dengan Pendukung Struktur Modal - Irawan, Sandi (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
This research explores the complex dynamics between asset structure, sales growth, and business risk in the context of stock pricing, taking into account the significant role played by capital structure. This phenomenon is critical in facing the challenges of dynamic financial markets, where the interaction of these variables can provide deep insight into stock market behavior. This research aims to understand the relationship between asset structure, sales growth and business risk in their influence on stock prices. This research approach involves associative quantitative analysis. to identify the relationship between the variables studied. The empirical data used comes from the financial reports of selected companies listed on the stock market. Research findings show that there is a significant relationship between asset structure, sales growth and business risk in influencing share prices. Capital structure is identified as a supporting factor that moderates this relationship, providing further understanding of the share pricing mechanism.